Analysis on the Semantics, Syntax, Equivalence, Fluency and Authenticity of Seif Salum’s Poem Entitled “Ewe Bibi Mwenye Enzi” Translated into English as “This Love” - Juma D. Imamu (Indonesian Journal of English Language Studies (IJELS), 2017)
This paper analyses the semantics, syntax, equivalence, fluency and authenticity of the translation of a Swahili poem entitled “Ewe Bibi Mwenye Enzi” by Seif Salum which was translated into English by the poetry translation workshop from the site http://www.poetrytranslation.org/poems/in/swahili/P12 as “This Love”. The introductory part discusses and pays recognition to the concept of untranslatability of the poetry where writers, such as Adam Czerniawski, Hatim Basil and Munday Jeremy, second the idea that poetry is untranslatable since poetry is a reflection of a particular society. Poetry also uses language but language is the reflection of people’s definition of their immediate environment, hence in that sense poetry is untranslatable since different societies have different views of their environments and the world. However, due to the increased curiosity which is partly a result of globalization of the world, people want to have diverse knowledge of everything. This makes it necessary to translate poetry anyway. In this case, poems, such as this one, have also been translated. Therefore, this paper tries to make analysis on how the change of language from Swahili to English have affected the semantics, syntax, equivalence, fluency and authenticity of the style and message of the poem.